Effectiveness of clinical Pilates and home exercises in sagittal cervical disorientation: randomized controlled study - Hurer, Cemaliye; Angin, Ender; Tuzun, Emine Handan (Future Medicine Ltd, 2021)
Aim: To compare effects of clinical Pilates and home exercises on postural disorders, strength and endurance of deep cervical flexors (DCF), cervical range of motion (CROM), pain intensity and functional disability in sagittal cervical disorientation. Patients & methods: Fourty six patients were included and divided into two groups. Clinical Pilates group performed stabilization based exercise and home exercise group performed conventional exercises. Results: Craniovertebral, head tilt, cervicothoracic angles and strength and endurance of DCF muscles had improvement in favor of clinical Pilates group (p < 0.05). There was no difference between groups in terms of right-left acromial distance, pain intensity, functional disability and CROM parameters (p > 0.05). Conclusion: Clinical Pilates exercises have been found to provide clinically significant improvements in craniovertebral, head tilt, cervicothoracic angles and strength and endurance of DCF muscles. However, in the increase of CROM, decreasing pain severity and functional impairment parameters there was no superiority of both exercise training.
Keywords: cervical disorientation; clinical Pilates; exercise; forward head posture; home exercise program; posture